In situ surface-trap passivation of CuBi2O4 photocathodes for unbiased solar water splitting. Issue 1 (12th December 2022) - Hu, Yingfei; Wang, Jun; Huang, Huiting; Feng, Jianyong; Liu, Wangxi; Guan, Hangmin; Hao, Lingyun; Li, Zhaosheng; Zou, Zhigang
Abstract : In situ developed MgO nanoparticle segregations are found to serve as effective surface-trap passivators for CuBi2 O4 photocathodes. Abstract : Passivating surface traps plays a crucial role in mitigating the efficiency loss of solar water-splitting electrodes. However, the associated surface-trap passivation approaches require the introduction of an overlayer, complicating the fabrication process and increasing the capital cost of photoelectrodes. Herein, using CuBi2 O4 as a prototype, an in situ surface-trap passivation strategy is developed, which yields a beneficial 90 mV anodic shift in hydrogen-evolution onset. Detailed mechanism investigations prove that the intentionally added Mg 2+ ions in the precursor gradually segregate as MgO and enrich at the grain boundaries/surface of the CuBi2 O4 multicrystalline, porous film during annealing, via which surface traps stemming from dangling bonds are spontaneously passivated; measurements of photovoltage generation characteristics and carrier lifetime validate the favorable roles of the MgO passivator in CuBi2 O4 photocathodes. A bias-free water-splitting device is assembled using MgO-passivated CuBi2 O4 and Mo-doped BiVO4 as the photocathode and photoanode respectively in a tandem configuration, delivering a solar-to-hydrogen conversion efficiency of approximately 0.41%.